Pengaruh Substitusi Tepung Terigu Dengan Kombinasi Tepung Jantung Pisang (Musa paradisiaca) dan Tepung Rumput Laut (Eucheuma cottonii) Terhadap Mutu Gizi Mi Basah - Nabila Khanza; I wayan Sweca Yasa; Dewa Nyoman Adi Paramartha (Jurnal Teknologi dan Mutu Pangan, 2023)
Wet noodle are food products that originally made from wheat flour with or without the addition of other ingredients and food additives. However, the main ingredient of wheat flour has nutritional value and low fiber content. The research aim was to investigate the best proportion of the wheat flour, banana blossom and seaweed of Eucheuma cottonii flour on a wet noodles quality. The experiments were conducted in laboratory and arranged with a Completely Randomized Design of single factor namely substitution of banana blossom flour with 5 types of proportions consisting 3 types of flour were wheat flour: banana blossom flour: seaweed flour with a ratio of 100 :0:0 (P0), 80:10:10 (P1), 70 :20 :10 (P2), 60:30 :10 (P3), 50:40:10 (P4), and 40:50:10 (P5) and three replications to obtain 18 experimental units. Data were analysed with analyses of variance at 5 percent of significancy and the post hoc test with Least Significant Difference Test (LSD). The results showed that the proportion affected significantly on all parameters of wet noodle quality. The best quality of a wet noodle were obtained from the proportion of 80 percent of wheat flour, 10% banana blossom flour and 10% of seaweed flour. The wet noodle had moisture, ash, protein, crude fiber, cooking loss, water absorption, L value and 0Hue of 31.38%, 1.28%, 5.4%, 1.69%, 47.23, 34.78 and 72.83 respectively. However, the sensory attributes were not preferred.